Geopolitical Challenges and the Macedonian Path to EU Accession - Zhidas Daskalovski (Međunarodni Problemi, 2023)
While formally founded on a variety of values and rules, the enlargement of the European Union (EU) has also been consistently influenced by geopolitical considerations, including within the Western Balkans (WB). The author particularly focuses on the Macedonian case in this regard, observing it in the context of the enlargement policy’s diminished credibility, the lack of progress towards fulfilling membership criteria, and more recently, the complications caused by Russia’s invasion of Ukraine. Apart from the veto imposed by Greece due to the naming dispute (which began in 2005), Skopje’s progress towards EU accession was further hindered by additional challenges related to democratic regression, state capture, and corruption. However, even the change of government and the subsequent conclusion of the Prespa Agreement with Athens in 2018 failed to result in the initiation of EU accession negotiations, which were initially blocked by France and later by Bulgaria. Meanwhile, concerns regarding the high degree of corruption persisted, while Bulgarian bilateral demands became integrated into the broader EU expectations from Skopje. The author concludes that the Macedonian case is characterized by a significant degree of bilateral and geopolitical considerations, further undermining the legitimacy and objectives of the enlargement policy.